Motility of Living Cells - Cappuccinelli, P. author. aut Link
80 p. 16 illus.
Keywords: Philosophers through the ages have made the astute observation that life, in its many aspects, appears to be continuously moving. All things in the universe, from the cosmic to the atomic level, exhibit some form of movement. Getting down to earth, the capacity to move is also an essential feature of the biological world. Movement was in fact synonymous with life at the time that Antony van Leeuwenhoek made the first simple microscope (seventeenth century). Using his primitive instrument he observed micro-organisms. which he called 'animalcules', swimming through a drop of water, and therefore he proclaimed that they 'seem to be alive'. We now know that movement in this form is not a prerequisite for life. although it is a crucial aspect in many living organisms. Realizing the general importance of motility in the biological world, this book will try to focus on the motility at a cellular level. Motility at a cellular level can take one of several forms: movement of components within the cell itself or movement of the cell as a whole (cell locomotion).